The impact of automation on workload and dispensing errors in a hospital pharmacy. (11th September 2012) - James, K. Lynette; Barlow, Dave; Bithell, Anne; Hiom, Sarah; Lord, Sue; Pollard, Mike; Roberts, Dave; Way, Cheryl; Whittlesea, Cate
Abstract Objectives To determine the effect of installing an original‐pack automated dispensing system (ADS) on dispensary workload and prevented dispensing incidents in a hospital pharmacy. Methods Data on dispensary workload and prevented dispensing incidents, defined as dispensing errors detected and reported before medication had left the pharmacy, were collected over 6 weeks at a National Health Service hospital in Wales before and after the installation of an ADS. Workload was measured by non‐participant observation using the event recording technique. Prevented dispensing incidents were self‐reported by pharmacy staff on standardised forms. Median workloads (measured as items dispensed/person/hour) were compared using Mann–Whitney U tests and rate of prevented dispensing incidents were compared using Chi‐square test. Spearman's rank correlation was used to examine the association between workload and prevented dispensing incidents. A P value of ≤0.05 was considered statistically significant. Key findings Median dispensary workload was significantly lower pre‐automation (9.20 items/person/h) compared to post‐automation (13.17 items/person/h, P < 0.001). Rate of prevented dispensing incidents was significantly lower post‐automation (0.28%) than pre‐automation (0.64%, P < 0.0001) but there was no difference (P = 0.277) between the types of dispensing incidents. A positive association existed between workload and prevented dispensing incidents both pre‐ (ρ = 0.13, P = 0.015) and post‐automation (ρ = 0.23, P < 0.001). Dispensing incidents were found to occur during prolonged periods of moderate workload or after a busy period. Conclusion Study findings suggest that automation improves dispensing efficiency and reduces the rate of prevented dispensing incidents. It is proposed that prevented dispensing incidents frequently occurred during periods of high workload due to involuntary automaticity. Prevented dispensing incidents occurring after a busy period were attributed to staff experiencing fatigue after‐effects.